Alkali-activated solid waste powder activity evaluation method based on response surface analysis
Through the method based on response surface analysis, the standard for the activity of solid waste powder is determined, and the problem of difficulty in evaluating the activity of solid waste in the prior art is solved, and the reasonable evaluation of any solid waste powder including low-active solid waste powder is achieved, which has practical application value.
Patent Information
- Application Number
- CN202411927271.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively evaluate the activity of solid waste, especially low-reactive solid waste powder, which has no obvious impact on the structure and performance of alkali-activated gelling materials, resulting in inconsistent performance of the materials in actual applications.
Using a response surface analysis method, by determining the main variables (such as NaOH solution concentration, gouache ratio and curing humidity) and response amount (such as 28d compressive strength), designing the experimental plan and conducting multiple regression analysis, obtaining the fitted model and regression equation, adjusting the main variables to match the prediction results, and determining the standard for the activity of solid waste powder.
This method can effectively avoid errors in the existing activity evaluation methods, provide a consistent and reasonable evaluation of solid waste powder activity. It is suitable for any solid waste powder including low-active solid waste powder, and has the characteristics of simple operation and low price.
Smart Images

Figure BDA0005209527660000071 
Figure BDA0005209527660000091 
Figure BDA0005209527660000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alkali-activated gelling materials, and in particular to a method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis. Background Art
[0002] Ordinary Portland cement (OPC) has become the most widely used building material due to its excellent performance. Due to the needs of transportation and other civil engineering facilities, the production and use of OPC in my country has been at a high level for many years. According to surveys, the production of 1 ton of OPC will produce about 1 ton of CO2, and the CO2 emissions from global OPC industrial production account for 5-8% of global greenhouse gas emissions. At the same time, the mining of OPC raw materials and the "two grinding and one burning" process consume a lot of electricity and coal resources. Every ton of cement produced consumes 112 kilograms of standard coal. On the other hand, my country produces a large amount of industrial solid waste every year in the process of industrial production and urban construction, and there are still a large number of solid wastes such as red mud and coal gangue that have not been effectively utilized. In the context of energy conservation and emission reduction, the high energy consumption and high pollution of cement and lime production have become increasingly prominent. Therefore, there is an urgent need for an environmentally friendly cementitious material with low pollution, low energy consumption, high performance and effective utilization of solid waste.
[0003] Alkali-activated cementitious materials are a new type of environmentally friendly inorganic material that has been widely studied in recent years. They have the advantages of early strength, fast hardening, high strength, and good durability, and can improve the utilization rate of solid waste. However, the diversity of solid waste components leads to significant differences in their activity, which has significantly different effects on the structure and properties of alkali-activated cementitious materials, thereby affecting the performance of the materials in practical applications.
[0004] At present, the traditional activity evaluation methods are mainly divided into chemical test methods and mechanical test methods. The chemical methods mainly include saturated lime test, Frattini test, Chapelle test and R 3 Tests, all of which are measured by monitoring the consumption of Ca(OH)2 or the generation of hydration heat, however, these methods are not applicable to low-activity solid wastes. Mechanical test methods evaluate the activity level by testing the compressive strength. Although the strength evaluation can intuitively reflect the overall volcanic ash activity of the material, it does not take into account the influence of test factors and conditions on the compressive strength. The current activity evaluation methods have not yet provided consistent conclusions in evaluating the activity of solid wastes and their influence on the compressive strength of alkali-activated cementitious materials. Therefore, how to reasonably evaluate the activity of solid wastes is an urgent problem to be solved in the prior art. Summary of the invention
[0005] The purpose of the present invention is to provide a method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis. The method is simple to operate and inexpensive, and can well avoid the disadvantages of the existing activity evaluation methods, such as the difficulty in evaluating low-activity solid waste and the errors caused by experimental factors and conditions. The method can be used as a comprehensive, intuitive and reasonable method for evaluating the activity of solid waste powder, and has practical application value.
[0006] To achieve the above object, the present invention provides a method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis, comprising the following steps:
[0007] Step 1: Grind the solid waste powder and dry it in an oven;
[0008] Step 2, preparing an alkali activator;
[0009] Step 3: Use the response surface method and determine the main variables and response quantities in the response surface method;
[0010] Step 4: Design an experimental plan according to the response surface methodology and conduct the experiment to obtain the experimental results;
[0011] Step 5: Perform multiple regression analysis on the test results to obtain the fitting model and regression equation;
[0012] Step 6: Conduct significance test to verify the fitting results;
[0013] Step 7: Determine the expected value of the response quantity that meets the response quantity requirements, and combine the expected value to obtain the theoretical optimal value of the main variable;
[0014] Step 8. Select a suitable main variable, conduct the experiment with the experimental plan in step 4, and calculate the predicted result based on the regression equation obtained in step 5. If the test result is consistent with the predicted result, the expected value of the response amount is used as the standard for evaluating the activity of solid waste powder. Otherwise, adjust the main variable and repeat step 3.
[0015] Preferably, the solid waste powder in step 1 is passed through a 75 μm square hole sieve after grinding, the part above 75 μm is sieved out, and then dried in an oven at 105° C. for 24 hours.
[0016] Preferably, the alkaline activator in step 2 is a NaOH solution prepared by mixing NaOH particles with distilled water, wherein the purity of the NaOH particles is 96% and the molecular weight is 40.
[0017] Preferably, the main variables in step three are NaOH solution concentration, water-to-powder ratio and curing humidity.
[0018] Preferably, the response quantity in step three is the 28d compressive strength, in MPa.
[0019] Preferably, the test process in step 4 is: first pre-stir the solid waste powder for 2 minutes, then gradually add the NaOH solution to the powder and stir slowly for 2 minutes, and then stir quickly for 1 minute; then, quickly pour the mixture into a 40mm×40mm×40mm cubic mold, and place it at room temperature of 20±1°C for 24 hours, finally demold and store it in a standard curing room at 20±2°C under specified humidity conditions for curing, until the compressive strength is measured at the age of 28 days.
[0020] Preferably, the fitting equation in step 5 is Among them, y is the response function, β0, β i , β 2i and β ij is the coefficient of each term of the polynomial, x i 、x j is the main variable, n is the number of main variables, i and j are index variables.
[0021] Preferably, in step six, a P test is used to perform a significance test and verification. If P<0.01, the model is significant and the fitting result is valid. Otherwise, the main variable is reselected for fitting calculation.
[0022] Preferably, the response quantity in step seven is required to be the maximum 28d compressive strength.
[0023] Preferably, the condition for the test result in step eight to be consistent with the prediction result is that the relative error is within 5%.
[0024] Therefore, the present invention adopts the above-mentioned alkali-activated solid waste powder activity evaluation method based on response surface analysis, which is simple to operate and low in price. It can well avoid the disadvantages of the existing activity evaluation methods such as the difficulty in evaluating low-activity solid waste and errors caused by experimental factors and conditions. It can be used as a comprehensive, intuitive and reasonable method for evaluating the activity of solid waste powder to evaluate the activity of any solid waste powder including low-activity solid waste powder, and has practical application value.
[0025] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further illustrated by the following examples.
[0027] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0028] The present invention provides a method for evaluating the activity of alkali-excited solid waste powder based on response surface analysis. The method examines the interaction between the main variables based on response surface analysis to determine the expected value of the response amount, and uses the expected value as a standard for evaluating the activity of the solid waste powder. The method can evaluate the activity of any solid waste powder including low-activity solid waste powder, and specifically includes the following steps:
[0029] Step 1: Grind the solid waste powder and dry it in an oven. After grinding, pass the solid waste powder through a 75 μm square hole sieve to remove the part above 75 μm, and dry it in an oven at 105°C for 24 hours.
[0030] Step 2: prepare an alkaline activator, which is a NaOH solution prepared by mixing NaOH particles with distilled water, wherein the purity of the NaOH particles is 96% and the molecular weight is 40.
[0031] Step 3: Use the response surface methodology and determine the main variables and response quantities in the response surface methodology. The main variables are NaOH solution concentration, water-to-powder ratio and curing humidity, and the response quantity is 28d compressive strength in MPa.
[0032] Step 4. Design an experimental plan according to the response surface methodology and conduct the experiment to obtain the experimental results. The experimental process is as follows: first pre-stir the solid waste powder for 2 minutes, then gradually add the NaOH solution to the powder and stir slowly for 2 minutes, and then stir quickly for 1 minute; then, quickly pour the mixture into a 40mm×40mm×40mm cubic mold and place it at room temperature of 20±1℃ for 24 hours, finally demold and store it in a standard curing room at 20±2℃ under specified humidity conditions for curing, and measure the compressive strength at the age of 28 days.
[0033] Step 5: Perform multiple regression analysis on the test results to obtain the fitting model and regression equation. The fitting equation is: Among them, y is the response function, β0, β i , β 2i and β ij is the coefficient of each term of the polynomial, x i 、x j is the main variable, n is the number of main variables, i and j are index variables.
[0034] Step 6: Conduct a significance test to verify the fitting results.
[0035] Step 7: Determine the expected value of the response quantity that meets the response quantity requirements, and combine the expected value to obtain the theoretical optimal value of the main variable. The response quantity requirement is the maximum 28d compressive strength.
[0036] Step 8. Select a suitable main variable, conduct an experiment using the experimental scheme in step 4, and calculate the predicted results using the regression equation obtained in step 5. If the test results are consistent with the predicted results, and the relative error between the test results and the predicted results is within 5%, then the expected value of the response amount is used as the standard for evaluating the activity of solid waste powder. Otherwise, adjust the main variable and repeat step 3.
[0037] Example 1
[0038] The present invention provides a method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis, comprising the following steps:
[0039] Step 1: Fly ash (FA), recycled micro powder (RMP), red brick powder (RBP), coal gangue powder (CGP) and cement kiln dust (CKD) are selected as solid waste powders, and the solid waste powders are ground and dried in an oven.
[0040] Step 2: Select NaOH particles (purity of 96%, molecular weight of 40) and mix with distilled water to form an alkaline activator.
[0041] Step 3: Set the main variable and response quantity based on the response surface theory, and set the range of the main variable. The main variables are NaOH solution concentration, water-to-powder ratio and curing humidity, and the response quantity is the 28d compressive strength of the specimen.
[0042] Based on the range of the main variable setting, several groups of alkali-activated cementitious material mix proportions were taken; the NaOH solution concentration levels were set to 5 mol / L, 9 mol / L, and 12 mol / L, the water-powder ratio levels were set to 0.3, 0.35, and 0.4, and the curing humidity was set to 30%, 65%, and 95%. The Design expert software was used to select 17 groups of alkali-activated cementitious material mix proportions. The 17 groups of alkali-activated cementitious material mix proportions are shown in Table 1 below.
[0043] Table 1 Mix ratio of alkali-activated cementitious materials in compressive strength test based on response surface methodology
[0044]
[0045] The alkali-activated cementitious material is tested to obtain the response quantity, that is, the 28d compressive strength of the specimen.
[0046] Step 4: Test the alkali-activated gelling material. The specific operation is as follows: first dry-mix the solid waste powder in a mixer for 2 minutes, then add the NaOH solution and stir slowly for 2 minutes and then stir quickly for 1 minute to obtain a mixture; then, quickly pour the mixture into a cubic mold (40mm×40mm×40mm) and place it at room temperature (20±1℃) for 24 hours. Finally, demould and store it in a standard curing room (20±2℃) under specified humidity conditions for curing until the compressive strength is measured at 28 days of age.
[0047] Step 5: Fit the measurement results of the main variable and the response quantity with a quadratic model to obtain a fitting equation;
[0048] The fitting equation of 28d compressive strength is:
[0049] y FA =1.9535*A+780.4897*B+0.1878*C-0.89*AB-0.0023*AC+0.1312*BC
[0050] -0.0619*A 2 -1121.2216*B 2 -0.0016*C 2 -141.2721
[0051] y RMP =2.0415*A+119.9017*B+0.1182*C-0.868*AB-0.0012*AC-0.0466*BC
[0052] -0.0964*A 2 -147.088*B 2 -0.0006*C 2 -22.5093
[0053] y RBP =0.5236*A+114.3079*B+0.0584*C-0.7387*AB+0.0011*AC-0.0342*BC
[0054] -0.0533*A 2 -203.2376*B 2 -0.0006*C 2 -11.1082
[0055] y CGP =1.704*A+214.4737*B+0.0505*C-1.927*AB-0.0007*AC+0.0052*BC
[0056] -0.0575*A 2 -299.0659*B 2 -0.0003*C 2 -37.4029
[0057] y CKD =1.1516*A+132.5003*B+0.2155*C-1.3646*AB-0.0031*AC-0.1189*BC
[0058] -0.0264*A 2 -150.5828*B 2 -0.0006*C 2 -26.4269
[0059] A, B, and C are respectively the concentration of NaOH solution, the water-to-powder ratio, and the curing humidity.
[0060] Step 6: Perform a significance test on the fitting results to ensure the significance of the model.
[0061] The significance test is verified by the variance test, which includes the standard deviation and the correlation coefficient R. 2 , P value test, the test results are shown in Table 2 below;
[0062] Table 228d Regression analysis test results of compressive strength
[0063] Solid waste powder type Fly ash Recycled Micro Powder Red brick powder coal gangue powder Cement kiln dust <![CDATA[R 2 ]]> 0.9746 0.9229 0.9545 0.9619 0.9638 P-value test <0.0001 0.0002 <0.0001 <0.0001 <0.0001
[0064] The results of regression analysis show that the 28d compressive strength model is significant.
[0065] Step 7: Taking the maximum value of 28d compressive strength as the optimization index, the expected value of the response quantity that meets the response requirements is obtained, and the theoretical optimal value of the main variable is obtained in combination with the expected value, as shown in Table 3 below;
[0066] Table 3 Expected values of 28d compressive strength of five alkali-activated cementitious materials
[0067]
[0068] Step 8. To verify the accuracy of the model, the measured value of the 28d compressive strength was compared with the predicted value calculated by the model under the conditions of 5 mol / L NaOH solution concentration, 0.35 water-to-powder ratio and 65% curing humidity. The test results are shown in Table 4:
[0069] Table 4 Prediction and measured results of 28d compressive strength of alkali activated cementitious materials
[0070]
[0071] The error does not exceed 5%, so it can be considered that the test results are in good agreement with the predicted results. Therefore, the expected value of the response amount is used as the standard for evaluating the activity of solid waste powders. The powders with the highest activity level are cement kiln dust, recycled micropowder, fly ash, red brick powder, and coal gangue powder.
[0072] Therefore, the present invention adopts the above-mentioned alkali-activated solid waste powder activity evaluation method based on response surface analysis, which is simple to operate and low in price. It can well avoid the disadvantages of the existing activity evaluation methods such as the difficulty in evaluating low-activity solid waste and errors caused by experimental factors and conditions. It can be used as a comprehensive, intuitive and reasonable method for evaluating the activity of solid waste powder, and has practical application value.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis, characterized in that: The following steps are involved: Step 1: Grind the solid waste powder and dry it in an oven; Step 2, preparing an alkali activator; Step 3: Use the response surface method and determine the main variables and response quantities in the response surface method; Step 4: Design an experimental plan according to the response surface methodology and conduct the experiment to obtain the experimental results; Step 5: Perform multiple regression analysis on the test results to obtain the fitting model and regression equation; Step 6: Conduct significance test to verify the fitting results; Step 7: Determine the expected value of the response quantity that meets the response quantity requirements, and combine the expected value to obtain the theoretical optimal value of the main variable; Step 8. Select a suitable main variable, conduct the experiment with the experimental plan in step 4, and calculate the predicted result based on the regression equation obtained in step 5. If the test result is consistent with the predicted result, the expected value of the response amount is used as the standard for evaluating the activity of solid waste powder. Otherwise, adjust the main variable and repeat step 3.
2. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 1, characterized in that: The solid waste powder in step 1 was ground and passed through a 75 μm square hole sieve to remove the part above 75 μm, and then dried in an oven at 105° C. for 24 h.
3. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 1, characterized in that: The alkaline activator in step 2 is a NaOH solution prepared by mixing NaOH particles with distilled water, wherein the purity of the NaOH particles is 96% and the molecular weight is 40.
4. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 1, characterized in that: The main variables in step three are NaOH solution concentration, water-powder ratio and curing humidity.
5. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 1, characterized in that: The response quantity in step 3 is the 28d compressive strength in MPa.
6. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 3, characterized in that: The test process in step 4 is as follows: first pre-stir the solid waste powder for 2 minutes, then gradually add the NaOH solution to the powder and stir slowly for 2 minutes, and then stir quickly for 1 minute; then, quickly pour the mixture into a 40mm×40mm×40mm cubic mold and place it at room temperature of 20±1℃ for 24 hours, finally demold and store it in a standard curing room at 20±2℃ under specified humidity conditions for curing until the compressive strength is measured at the age of 28 days.
7. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 1, characterized in that: The fitting equation in step 5 is Among them, y is the response function, β0, β i , β 2i and β ij is the coefficient of each term of the polynomial, x i 、x j is the main variable, n is the number of main variables, i and j are index variables.
8. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 1, characterized in that: In step six, the P test is used for significance test verification. If P < 0.01, the model is significant and the fitting result is valid. Otherwise, the main variable is reselected for fitting calculation.
9. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 1, characterized in that: The response quantity required in step seven is the maximum 28d compressive strength.
10. The method for evaluating the activity of alkali-activated solid waste powder based on response surface analysis according to claim 1, characterized in that: The condition for the test results in step eight to match the predicted results is that the relative error is within 5%.
Citation Information
Patent Citations
Response surface theory-based geopolymer composite material mix proportion design method
CN115656484A
Alkali-activated slag-tanning sludge curing agent and mix proportion optimization method thereof
CN116063018A
Strength activity evaluation method for activity of tuff volcanic ash material
CN118609720A